Targeting Ferroptosis: Pathological Mechanism and Treatment of Ischemia-Reperfusion Injury - Xinye Li (Hindawi Limited, 2021)
Ischemia-reperfusion (I/R) is a pathological process that occurs in many organs and diseases. Reperfusion, recovery of blood flow, and reoxygenation often lead to reperfusion injury. Drug therapy and early reperfusion therapy can reduce tissue injury and cell necrosis caused by ischemia, leading to irreversible I/R injury. Ferroptosis was clearly defined in 2012 as a newly discovered iron-dependent, peroxide-driven, nonapoptotic form of regulated cell death. Ferroptosis is considered the cause of reperfusion injury. This discovery provides new avenues for the recognition and treatment of diseases. Ferroptosis is a key factor that leads to I/R injury and organ failure. Given the important role of ferroptosis in I/R injury, there is considerable interest in the potential role of ferroptosis as a targeted treatment for a wide range of I/R injury-related diseases. Recently, substantial progress has been made in applying ferroptosis to I/R injury in various organs and diseases. The development of ferroptosis regulators is expected to provide new opportunities for the treatment of I/R injury. Herein, we analytically review the pathological mechanism and targeted treatment of ferroptosis in I/R and related diseases from the perspectives of myocardial I/R injury, cerebral I/R injury, and ischemic renal injury.